The interplay between L2 students’ self-efficacy and engagement in English medium instruction classes - Tham My Duong; Sum Truong Do; Thao Quoc Tran (Universitas Syiah Kuala, 2026)
English Medium Instruction (EMI) has been adopted in various training programs, as it is believed to enhance students’ English proficiency and subject knowledge; however, research on EFL students’ self-efficacy and engagement in EMI in EFL contexts remains underexplored. This study aimed to explore the levels of self-efficacy and engagement among foreign language (L2) students in EMI classes at a Vietnamese tertiary institution and examine the relationship between these two aspects. Specifically, an embedded mixed-methods design combining quantitative survey data from 173 L2 students with qualitative semi-structured interviews from 10 participants was employed. The findings revealed that L2 students displayed moderate self-efficacy in EMI contexts, with variations across distinct self-efficacy elements, resulting in varied levels of engagement. The results also indicated that reinforcing students’ confidence through clear goal-setting, constructive feedback, and anxiety-diminishment strategies could foster higher levels of engagement in EMI settings. Additionally, a strong, positive, and statistically significant correlation between L2 students’ self-efficacy and their engagement in EMI classes was found. This study concluded that L2 students’ self-efficacy strongly influenced their engagement in EMI contexts, and their high levels of confidence could enhance their participation and learning outcomes. Pedagogical recommendations are also discussed to enhance the effectiveness of EMI in light of relevant learning factors.